Teacher Instructional Strategies to Enhance Student Learning Interest in Primary Science and Social Learning - Tri Astuti Tungga Dewi; Nashrullah Nashrullah; Surahman Wilade; Rizal Rizal; Ryan Andhika Pratama (Papanda Publisher, 2026)
Student learning interest plays a crucial role in determining engagement and achievement in primary education, particularly in integrated subjects such as Science and Social Learning. However, classroom practices that rely on monotonous instructional approaches may reduce students’ motivation and active participation. This study aims to explore teacher instructional strategies used to enhance student learning interest in a Grade IV primary classroom. A qualitative descriptive design was employed to capture in-depth insights into classroom practices. Data were collected through classroom observations, semi-structured interviews with the classroom teacher, and documentation of learning activities. The findings reveal several key strategies that contributed to increased student interest: variation in instructional methods (experiments, discussions, and questioning), integration of digital media such as Smart TV–based learning applications, experiential and game-based activities, contextualization of learning materials to students’ daily lives, and the use of positive reinforcement through praise and small rewards. In addition, continuous teacher reflection and adaptation of instructional approaches were identified as essential in sustaining student engagement. Despite these efforts, challenges such as student absenteeism due to health issues occasionally disrupted learning continuity, requiring collaboration between teachers and parents. Overall, the study highlights the importance of diverse, student-centered instructional strategies in fostering learning interest in primary Science and Social Learning contexts. These findings provide practical insights for teachers seeking to create more engaging and meaningful learning environments in primary classrooms.